Sex-specific associations in verbal memory brain circuitry in early psychosis. (July 2022) - Buck, Gabriella; Makowski, Carolina; Chakravarty, M.Mallar; Misic, Bratislav; Joober, Ridha; Malla, Ashok; Lepage, Martin; Lavigne, Katie M.
Abstract: Hippocampal circuitry and related cortical connections are altered in first episode psychosis (FEP) and are associated with verbal memory deficits, as well as positive and negative symptoms. There are robust sex differences in the clinical presentation of psychosis, including poorer verbal memory in male patients. Consideration of sex differences in hippocampal-cortical circuitry and their associations with different behavioral dimensions may be useful for understanding the underlying pathophysiology of verbal memory deficits and related symptomatology in psychosis. Here, we use a data-driven approach to simultaneously capture the complex links between sex, verbal memory, symptoms, and cortical-hippocampal brain metrics in FEP. Structural magnetic resonance imaging and behavioral data were acquired from 100 FEP patients (75 males, 25 females) and 87 controls (55 males, 32 females). Multivariate brain-behavior associations were examined in FEP using partial least squares to map sociodemographic, verbal memory, and clinical data onto brain morphometry. The analysis identified two sex-dependent patterns of verbal memory, symptoms, and brain structure. In male patients, verbal memory deficits and core psychotic symptoms were associated with both increased and decreased frontal and temporal cortical thickness and reductions in CA2/3 hippocampal subfield and fornix volumes. In female patients, fewer negative/depressive symptoms were associated with a more attenuated cortical thickness pattern and more diffuse reductions in hippocampal white matter regions. Taken together, the results contribute towards better understanding the underlying pathophysiology of psychosis by highlighting the unique contribution of specific hippocampal subfields and surrounding white matter and their connections with broader cortical networks in a sex-dependent manner. Graphical abstract: Image 1 Highlights: Sex-dependent brain alterations may subserve sex differences in psychosis pathology. A data-driven approach links brain-behavior associations in early psychosis. Greater cortical alterations and psychosis symptoms in male-dependent pattern. Greater hippocampal subfield reductions and less severe pathology in female pattern. Integrating sex in neuroimaging and clinical research in psychosis is crucial.